Evaluation and early warning of water environment carrying capacity in Liaoning province based on control unit: A case study in Zhaosutai river Tieling city control unit - Yujie Zhang (Elsevier, 2021)
Water environment carrying capacity (WECC) is an important index to investigate the carrying capacity of water environment to human life and production. In this study, the index system method and system dynamics method were combined to calculate the water environment carrying capacity. Zhaosutai river Tieling city control unit was chosen for deteriorated water environment and the water environment carrying capacity was evaluated and early warned. The water environment carrying capacity of Zhaosutai river Tieling city control unit is calculated from 2012 to 2035, with the maximum value of 0.7817 in 2018 and the minimum value of 0.3300 in 2013. From 2020 to 2035, it is predicted that the water environment carrying capacity of Zhaosutai river Tieling city control unit will be changed from light warning to moderate warning. Through the multi-scenario simulation of four scenarios, it can be found that it is more beneficial to improve the water environment carrying capacity to limit the social and economic development while reducing the emission of pollutants. It provides an effective scientific reference for the government to coordinate environmental protection and economic development.